Testosterone and Depression in Aging Men - Stuart N. Seidman; B. Timothy Walsh (1999)
In men, testosterone secretion affects neurobehavioral functions such as sexual arousal, aggression, emotional tone, and cognition. Beginning at approximately age 50, men secrete progressively lower amounts of testosterone; about 20% of men over age 60 have lower-than-normal levels. The psychiatric sequelae are poorly understood, yet there is evidence of an association with depressive symptoms. The authors reviewed 1) the physiology of the hypothalamic-pituitary-gonadal axis and its changes with age in men; and 2) the evidence linking testosterone level and major depression in men. Data on this relationship are derived from two types of studies: observational studies comparing testosterone levels and secretory patterns in depressed and non-depressed men, and treatment studies using exogenous androgens for male depression. The data suggest that some depressed older men may have state-dependent low testosterone levels and that some depressed men may improve with androgen treatment.